Wood Permeability Assessment of Young Teak (Tectona grandis L.f.) - Ratih Damayanti; Krisdianto Krisdianto; Jugo Ilic; Gustan Pari; Peter Vinden; Barbara Ozarska (Masyarakat Peneliti Kayu Indonesia, 2020)
Wood properties of young teak (Tectona grandis L.f.) is inferior, and then preservative treatment is one possible solution to enhance its service life. The uptake and movement of preservatives through wood cell structure is directly connected to the wood permeability. There are two simple methods to identify wood permeability: water soaking and bubble test methods. This paper assesses the young teak permeability by water soaking and bubble test methods. The assessment was conducted into five cm thick young-teak discs by soaking in the red-dye water and blowing air into the discs which had been coated with soap. Results show that the heartwood is less permeable than sapwood. Red-dye penetrates almost 100% of the sapwood area, and the red-dye did not penetrate in the heartwood. Red-dye only penetrates in the cracked heartwood through the void volume in the cracking heartwood. There is a transition zone between sapwood and heartwood, and it is refractory. Bubble test with air pressure from compressor could open the air-pathway in the heartwood and sapwood of young-teak discs taken from Bogor. The bubble test result of young-teak discs from Madiun showed air-pathway only in the sapwood, but heartwood. The air pressure is not capable of moving the vapour through the wood cell. It indicates that the heartwood of young-teak from Madiun is less permeable and less possibility for pressure treatment.